2021
DOI: 10.1371/journal.pone.0252064
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common mental disorders and associated factors among adults with Glaucoma attending University of Gondar comprehensive specialized hospital tertiary eye care and training center, Northwest, Ethiopia 2020

Abstract: Purpose This study aimed to assess the prevalence of common mental disorders and associated factors among adults with glaucoma at Gondar university comprehensive specialized hospital tertiary eye care and training center. Glaucoma predisposes patients to common mental problems and leads to wasteful, costly and inefficient use of medical services and complications of the diagnoses. So, determining the level and factors associated with common mental disorders among glaucoma patient would help to improve and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…[ 5 ] Findings from various studies have shown that glaucoma is associated with low levels of psychosocial well-being characterized by a diminution in the individual’s perception of self and ability to function in the community and usually manifests as depression and/or anxiety. [ 6 7 8 9 10 ] Depressed people feel sad, empty, hopeless, worthless, and irritable with an aversion to activity. [ 11 12 13 14 ] Although anxiety is distinguished by feelings of precariousness and vulnerability, in severe cases, it comes with repeated apprehension and intense fear, which is incommensurate to the existing situation causing it.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Findings from various studies have shown that glaucoma is associated with low levels of psychosocial well-being characterized by a diminution in the individual’s perception of self and ability to function in the community and usually manifests as depression and/or anxiety. [ 6 7 8 9 10 ] Depressed people feel sad, empty, hopeless, worthless, and irritable with an aversion to activity. [ 11 12 13 14 ] Although anxiety is distinguished by feelings of precariousness and vulnerability, in severe cases, it comes with repeated apprehension and intense fear, which is incommensurate to the existing situation causing it.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, gender was found to have a significant effect on the mental health of glaucoma patients. An institution-based cross-sectional study conducted on 495 glaucoma patients indicated that the female sex (95% CI: 1.66–8.62) ( p = 0.001) was significantly associated with increased levels of common mental disorders in glaucoma patients ( Tilahun et al, 2021 ). It is in harmony with the study of Lim et al (2016) , reporting higher depression and anxiety in females than in male glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Social support has been found to be positively correlated with quality of life and glaucoma treatment adherence [42][43][44]. One study found that low social support among glaucoma patients was significantly associated with increased rates of mental health disorders [45], and this in turn can further increase vulnerability to vision loss [29].…”
Section: Discussionmentioning
confidence: 99%